Gender Comparison of Psychological Comorbidities in Tinnitus Patients – Results of a Cross-Sectional Study - Fioretti, Alessandra; Natalini, Eleonora; Riedl, David; Moschen, Roland; Eibenstein, Alberto (Frontiers in Neuroscience, 2020)
Background: Over the last few years, clinicians focused their attention on the gender-related features in patients with tinnitus, often leading to controversial results. An interesting aspect of tinnitus patients is linked to the complexity of clinical presentation, where besides audiological symptoms, other co-occurrence psychological disorders may complicate the diagnostic evaluation. Methods: Therefore, we studied 107 patients with tinnitus, investigating their psychological comorbidities in the light of gender differences. All patients were evaluated with ENT/audiological and psychological examination to consider presence/absence, type and gender distribution of psychopathological comorbidities. Patients completed questionnaires on tinnitus distress (Tinnitus Handicap Inventory, THI), anxiety (Beck Anxiety Inventory, BAI), depression (Beck Depression Inventory, BDI), metacognition (Metacognition Questionnaire-30, MCQ-30) and worry (Penn State Worry Questionnaire). The influence of gender on the relationship between tinnitus distress and psychological comorbidities was investigated with simple moderation analyses using the SPSS PROCESS macro. Results: The total sample included 65 male and 42 female patients (60.7% vs. 39.3%), matched for age and duration of tinnitus. We found no significant differences for tinnitus distress (THI total score, THI subscales) and MCQ-30 subscales, except for the control over thoughts, where men showed significantly higher scores than women (p=.045). Also, in our sample women showed significantly higher values for depression (BDI total score, p=.019), anxiety (BAI total score, p=.010) and worries (PSQW total score, p=.015). Moderation analyses revealed a significant influence of gender on the relationship of tinnitus distress with depression: higher scores of tinnitus distress were associated with significantly elevated levels of depression amongst men. No further gender influences could be observed in our sample. Discussion: In conclusion, our results indicate general gender differences for psychological comorbidities in tinnitus patients, with women reporting more depression, anxiety and worries. Men, on the other hand, showed a higher need to control their thoughts. Additionally, our results indicate that men might have more coping problems with increasing levels of tinnitus distress, leading to increased depressive symptoms. However, the question about the distinction between female and male patients remains an open area of research for future studies on tinnitus.